2015
DOI: 10.3923/pjbs.2015.240.246
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Responses of Six Grape Genotypes to NaCl Salt Stress

Abstract: A B S T R A C T Salt contaminated areas are considered as, a critical problem in arid and semi-arid regions that limit the yield potential of agricultural crops. In the present study, NaCl salt stress susceptibility was assessed in five Jordanian grapes landraces (Salti, Zani, Red Glob, Darawishi and SoriBaladi) and B41 root stock using two levels of salt stress (6000 and 12000 ppm NaCl) in addition to the control during 2013 and 2014 growing season under controlled condition. Plant biomass (root and shoot), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Whereas, Owais [6] reported morphological and physiological alterations induced in five grapevine landraces and B41 rootstock exposed to salt stress (9.4 dS/m and 18.8 dS/m NaCl). The previous study showed genotyping variation in salinity tolerance among the examined accessions.…”
Section: Cabernet Sauvignon Based On Quantitative Reverse Transcriptimentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, Owais [6] reported morphological and physiological alterations induced in five grapevine landraces and B41 rootstock exposed to salt stress (9.4 dS/m and 18.8 dS/m NaCl). The previous study showed genotyping variation in salinity tolerance among the examined accessions.…”
Section: Cabernet Sauvignon Based On Quantitative Reverse Transcriptimentioning
confidence: 99%
“…It has been documented that, approximately 50% of irrigated soil in Syria suffers from salinity [5]. Grapevine is classified to be moderately sensitive to salt stress [6]. Salinity among other environmental stresses causes deleterious effects in biological processes manifested by morphological, physiological, biochemical and molecular changes.…”
Section: Introductionmentioning
confidence: 99%